A new species of Telipogon (Orchidaceae: Oncidiinae) in the Central Peruvian Amazon - Valenzuela-Gamarra, Luis; Nauray-Huari, William (Phytotaxa, 2025)
A new species of Telipogon from the montane forests of the Oxapampa-Asháninka-Yánesha Biosphere Reserve, Pasco Region, Perú, is described and illustrated. This species was found growing on the slender branches of a Miconia tree at an elevation of between 2100 and 2300 m. similar to T. perlobatus. Telipogon yanesha sp. nov., differs by a much shorter inflorescence with a single flower at a time, a 1-veined labellum with an entire margin, the central lobe, and noticeably smaller lateral lobes. The species description is accompanied by illustrations and photographs, and information is provided on aspects of its distribution, phenology, ecology, and similarity to other species.